(untitled) (Journal of Parents and Teachers, 2019)
The Society of Jesus lays claim to a venerable tradition in the field of education. From its beginning in 1540, the Jesuits discovered, in their founding and development of educational centers an apostolic ministry which, though not contemplated among is initial pastoral activities, became a central feature of the newly founded Institute. They created an educational model that implanted, in all of its schools, one that was based on the Parisian model and the study of Humanities, a field of studies that also included the sciences. The schools charged no tuition and were models of adaptation, such was the Jesuit educational in its beginnings.